Representasi Tokoh Ibu dalam Novel Bila Esok Ibu Tiada Karya Nuy Nagiga serta Pemanfaatannya dalam Pembelajaran - Dumarista, Evi Yesifina; Rusmiyati, Rusmiyati (ppjbsip, 2025)
The purpose of this research is to describe the forms of representation of the character of Mother in this era through the novel. The object of this research is the character of Mother, focusing the analysis on the role, function, forms of representation, and its utilization in learning. This analysis uses Charles Sanders Peirce's semiotic theory, namely representamen, object, and interpretant. This research method uses descriptive qualitative and data analysis techniques in the form of reading and writing. Meanwhile, the credibility and dependability techniques use quotations of words, phrases, or sentences in the novel